Detection of selenoprotein transcriptome in chondrocytes of patients with Kashin–Beck disease - Gong, Yi; Wu, Yifan; Liu, Yanli; Chen, Sijie; Zhang, Feiyu; Chen, Feihong; Wang, Chaowei; Li, Shujin; Hu, Minhan; Huang, Ruitian; Xu, Ke; Wang, Xi; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: Kashin-Beck disease(KBD) is a deformed osteochondral disease with a chronic progression that is restrictively distributed in eastern Siberia, northern Korea and some areas of China and Selenium deficiency has been identified as an important factor in the pathogenesis of this disease in recent years. Objective: To investigate the selenoprotein transcriptome in chondrocytes and define the contribution of selenoprotein to KBD pathogenesis. Methods: Three cartilage samples were collected from the lateral tibial plateau of adult KBD patients and normal controls paired by age and sex, for real-time quantitative polymerase chain reaction (RT‒qPCR) to detect the mRNA expression of 25 selenoprotein genes in chondrocytes.. Six other samples were collected from adult KBD patients and normal controls, In addition, four adolescent KBD samples and seven normal controls were used for immunohistochemistry (IHC) to determine the expression of proteins screened by the result of RT‒qPCR that had a different gene levels. Results: Increased mRNA expression of GPX1 and GPX3 was observed in chondrocytes, and stronger positive staining was displayed in cartilage from both adult and adolescent patients. The mRNA levels of DIO1, DIO2 and DIO3 were increased in KBD chondrocytes, however, the percentage of positive staining decreased in KBD cartilage from adults. Conclusion: The selenoprotein transcriptome, mainly the glutathione peroxidase (GPX) and deiodinase (DIO) families, were altered in KBD and might play a vital role in the pathogenesis of KBD.